Pelatihan Ansambel Musik bagi Siswa – siswi Kelas X dan XI SMA Katolik Giovanni Kupang - Petrus Geraldino Resha Almi; Hubertus Lado Lewar; Alfonsia Maria Resaa; Maria Silvani Kupu Da; Agustinus Renaldus Afoan Elu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Ensemble music is a musical presentation consisting of a mixture of several musical instruments that contain rhythmic, melodic, and harmonious elements. Etymologically, the word ensemble comes from the French word ensemble which means group. An ensemble is also known as a musical ensemble that plays one or several types of musical instruments. In education at school, ensembles have a fairly important role in improving the quality of students' music. In addition to gaining theoretical ensemble knowledge, students are also directed to practice musical ensembles, so that they can channel their creativity in an ensemble game. The objectives of this ensemble training activity are: 1) Hone the musical skills of each individual 2) Create harmony between musical instruments 3) Prepare the ensemble group to be performed. The methods used in ensemble training are the drill method and peer tutors. The result of this activity is that students can have the ability to playing music ansambel.